Familiarizing Students with a Friendly Learning Activity in Enriching English Vocabulary: Memorization Technique - Khadijah Maming; Amir Patintingan; Sianna; Delfiana (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
In learning English, we must apply appropriate technique to mastery it. One of the technique used is memorizing vocabulary. The more vocabulary we memorize, the easier it will be for us to use the language in communicating. But not only memorization technique can improve our language learning but there are still many methods that we can use depending on how the learning or learning model is suitable for those learners. But in fact, based on the observations of researchers at SMP Negeri 2 Parepare, researchers found several problems in students' vocabulary mastery. One of the problems is the students still do not know various kinds of vocabulary such as adjectives, nouns, verbs and adverb, and how to arrange them in a sentence. In this study, the researchers applied a mixed method with a one group class pretest and posttest design. The researchers took one class as a sample where the number of students was thirty students. The results of data analysis showed that the memorization technique provided positive impacts on students’ English vocabulary. This is evidenced by the N-Gain test that aimed to see the effect of the treatment given, showing that there are four students in the high category, there are nineteen students in the currently/medium category, and there are seventeen students in the low category. In addition, the most of students responded memorization technique positively. It can be said that through the memorization technique, it can improve the vocabulary mastery of students at SMP Negeri 2 Parepare.